A Feasibility study of the escape-pain programme for patients with knee osteoarthritis in the Malaysian context: Preparation of a protocol - Che Hasan, Muhammad Kamil; Stanmore, Emma; Todd, Chris (IIUM Press, 2019)
Background: In Malaysia, around one in ten older people are diagnosed with osteoarthritis (OA), with the knee being one of the most commonly affected areas. This can lead to functional limitations, impaired activities of daily living and reduced quality-of-life. Thus, a systematic review of the literature concludes that a programme integrating exercise, education and active coping strategies, known as Enabling Self-management and Coping with Arthritic Pain using Exercise (ESCAPE-pain) provides the best evidence for patients with knee OA. Objective: Through Thus, this study aims to evaluate the feasibility of a randomised controlled trial to explore the implementation of the ESCAPE-pain programme among patients with knee OA in the Malaysian healthcare context guided by the UK Medical Research Council Framework (2000). Methods: This is a pragmatic, feasibility randomised controlled trial (RCT) recruiting patients (n=72) with knee osteoarthritis from two hospitals in Malaysia. Participants were randomised to receive ESCAPE-pain intervention plus usual care (n=36) (intervention group) or usual care only (n=36) (control group). The ESCAPE-pain programme was delivered twice weekly for six weeks by a certified trainer. Outcomes were measured for physical function (TUG), knee injury and osteoarthritis outcome scores (KOOS), mental wellbeing (Short-WEMWBS), exercise health beliefs and self-efficacy and fear of falling (Short-FES-I) at baseline, six-week and after 12-week of intervention. Results: This is the first study to evaluate the implementation in the Malaysian healthcare context. Conclusion: The findings are hoped to facilitate the practicality of the design of a definitive randomised controlled trial, to support people living with knee osteoarthritis in Malaysia.